2021
DOI: 10.20944/preprints202111.0491.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Models That Link and Suggest Data about Elementary Particles, Dark Matter, and the Cosmos

Abstract: We suggest progress regarding the following six physics opportunities. List all elementary particles. Describe dark matter. Explain ratios of dark matter to ordinary matter. Explain eras in the history of the universe. Link properties of objects. Interrelate physics models. We use models based on Diophantine equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…An interesting article suggests a specification for dark matter and modeling regarding dark-energy phenomena. It includes predications and suggesting a mechanism that might convert some energy associated with one of ordinary matter and dark matter to energy that would associate with the other one of ordinary matter and dark matter (34). A recent article found that J0613+52 has no stars.…”
Section: Ivd) Calculation Of the Derived Sdef Equations Parametermentioning
confidence: 99%
“…An interesting article suggests a specification for dark matter and modeling regarding dark-energy phenomena. It includes predications and suggesting a mechanism that might convert some energy associated with one of ordinary matter and dark matter to energy that would associate with the other one of ordinary matter and dark matter (34). A recent article found that J0613+52 has no stars.…”
Section: Ivd) Calculation Of the Derived Sdef Equations Parametermentioning
confidence: 99%